PENGARUH CASH HOLDING, PROFITABILITAS DAN FINANCIAL LEVERAGE TERHADAP NILAI PERUSAHAAN: Studi pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di BEI Tahun 2020-2022 - Ervita Puspita Sari; Tutut Dewi Astuti (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This research aims to analyze the influence of cash holdings, profitability and financial leverage on company value in manufacturing companies in the primary industry and chemical sectors listed on the Indonesia Stock Exchange (BEI) from 2020 to 2022. The aim of this research is to use multiple regression analysis to identify the relationship between the independent variable and the dependent variable, namely company value. The findings show that cash holdings do not have a significant impact on firm value, indicating that investors do not consider the level of a company's cash holdings when making investment decisions. In addition, financial leverage varies depending on the company's situation, but profitability as measured by return on assets (ROA) also does not have a positive impact on company value.These findings provide important insights for management as they develop financial strategies to increase shareholder value.